Yahoo Web Search

  1. Sort by

  1. If v is half of w: v = w/2 and u is the mean of v and w: u = (v + w) / 2 And you know it's a triangle...w = 80 Now that we have w we can solve for v and u: v + w = 120 v + 80 = 120 v = 40 u = (v + w...

    3 Answers · Science & Mathematics · 25/10/2019

  2. u = 8i + 7j → tan(u) = 7/8 v = 7i - j → tan(v) = - 1/7 tan(a - b) = sin(a - b) / cos(a - b) → recall...b)] / [1 + tan(a).tan(b)] → adapt this result to your case tan(u - v) = [tan(u) - tan(v)] / [1 + tan(u).tan(v)] tan(u - v) = [(7/8) - (- 1/7...

    2 Answers · Science & Mathematics · 29/04/2019

  3. v = ⟨a, b, c⟩ for example yields vv = a² + b² + c² = (√(a² + b² + c²))² = ||v||²

    3 Answers · Science & Mathematics · 04/08/2019

  4. v = sin(pi * t) s = (-1/pi) * cos(pi * t) + C s = 0 when t = -3 0 = (-1/pi) * cos(-3pi) + C 0 = (-1/pi) * (-1) + C 0 = 1/pi + C -1/pi = C s = (-1/pi) * cos(pi * t) - 1/pi s = (-1/pi) * (cos(pi * t) + 1)

    1 Answers · Science & Mathematics · 18/07/2019

  5. Integrate from t = 0 to t = 1 u = t^2 du = 2t * dt dv = e^(-3t) * dt v = (-1/3) * e^(-3t) (-1/3) * t^2 * e^(-3t) - (-2/3) * int(t * e^(-3t) * dt) => (-1/3...

    3 Answers · Science & Mathematics · 21/02/2019

  6. 8u - 8 = 4 - 4w 8u + 4w = 12 2u + w = 3 w = 3 - 2u w = u + v 3 - 2u = u + v v = 3 - 3u 8u = 4 + 6v 8u = 4 + 6 * (3 - 3u) 4u = 2 + 3 * (3 - 3u) 4u = 2 + 9 - 9u 13u = 11 u = 11/13 v = 3 - 3u v = 3 - 33/13 v = 39/13 - 33/13 v = 6/13 w = u + v w = 11/13 + 6/13 w = 17/13

    2 Answers · Science & Mathematics · 16/09/2019

  7. ...the photo comment*** So the first problem is to show that if x ∈ V(ε, a) and y ∈ V(ε, b) then x+y ∈ V(2ε, a+b). Most of...

    1 Answers · Science & Mathematics · 18/09/2019

  8. ... are consistent with the quadratic function f(v)=(v−2)(v−5). If v(0)>5 then initially f>0...2. The solution of this ODE is in fact v = ((2(v₀−5)e³ᵗ−5(v₀−2...

    1 Answers · Science & Mathematics · 10/02/2019

  9. The volume of a rectangular box is V = ℓ ⋅ w ⋅ h. For the box to satisfy certain requirements...

    3 Answers · Science & Mathematics · 12/02/2019

  10. dot product, then cross product u•v = 0, ⟨3,2,1⟩•⟨1,-1,-1⟩ = 3 - 2 - 1 = 0 so let v = ⟨1,-1,-1⟩ u×v = ⟨3...1,4,-5⟩ = w Check: u•w = ⟨3,2,1⟩•⟨-1,4,-5⟩ = -3 + 8 - 5 = 0 and v•w = ⟨1,-1,-1⟩•⟨-1,4,-5⟩ = -1 - 4 + 5 = 0 So all three vectors...

    1 Answers · Science & Mathematics · 06/09/2019

  1. Try asking your question on Yahoo Answers